Distribution and Assemblage Variation of Benthic Macroinvertebrates: A Uniform Elevational Biodiversity Pattern Among Different Groups? - Wang, Baoqiang; He, Yajing; Zhao, Yongjing; Cui, Yongde (Frontiers in Ecology and Evolution, 2022)
Biodiversity patterns along elevational gradient of vertebrates have been widely focused on in the previous studies, but it is still insufficient on invertebrates in the lakes at a wide elevational extent. Based on field samplings and literatures, we compared biodiversity patterns among different taxonomic groups of benthic macroinvertebrates in 104 lakes of China and India along an elevational gradient of 2 5,010 m a.s.l., and revealed the key driving factors, then discussed key mechanisms underlying elevational biodiversity patterns. We found that elevational biodiversity patterns of different taxonomic groups were not uniform, e.g., an exponentially decreasing pattern of Bivalvia, a first horizontal and then decreasing pattern of Gastropoda, and a linear decreasing pattern of Oligochaeta and Insecta. Elevation and elevation-controlled variables (temperature and salinity) were the key driving factors to biodiversity patterns. The effects of them were strongest on Bivalvia, and less on Gastropoda, whereas relatively weak on Oligochaeta and Insecta. Finally, we discussed three important mechanisms which shaped elevational biodiversity patterns and assemblage variations of benthic macroinvertebrates by linking our results with the classic hypotheses about biodiversity patterns, including climate/productivity, environmental heterogeneity, and dispersal/history. These results could improve our understandings of biodiversity patterns and biodiversity conservation.